The Ability of Scratch Teaching in Programming Language—Taking Roguelike Mathematical Games as an Example - Weng, Tingsheng (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
In recent years, Japan and Taiwan have begun to include programming education in the elementary and secondary school curriculum as well as in universities so as to strengthen students’ programming language ability. In this study, the Scratch programming language was used to design a roguelike mathematical game based on a prince saving a princess in a forest. Mathematics refers to the positioning of each object, its XY coordinates, movement and distance, positive and negative movement angles, waiting time (seconds), and speed. In this study, the mathematical game program was provided to a class of rural elementary school students in southern Taiwan. By imitating the design, the teachers, and students can work together on this hands-on programming project to design the pictures, cooperate in discussing and solving the programming dilemma, and enjoy the game together. The elementary school principals and teachers who participated in the scene observed and concluded that it allowed the pupils to think seriously, enjoy discussing the integration of mathematics and programming, design digital games, and develop the final result of roguelike digital games. This project allowed students to take on the challenge of learning to write programs with curiosity and learn to use different building block programming languages in Scratch to produce a program by imitation. Students can also learn to change and add objects, and arrange the things to be done by different characters through programming. The mathematical roguelike challenges let the students understand the learning achievements through the taste of each victory. Through the game attraction, this study fostered cross-domain digital talents in areas such as digital technology, program education, and artificial intelligence.